2020
DOI: 10.1111/bph.15031
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fatty acid amide hydrolase in the CNS prevents and reverses morphine tolerance in male and female mice

Abstract: Background and Purpose: Fatty acid amide hydrolase (FAAH) is an intracellular serine amidase that terminates the signalling of various lipid messengers involved in pain regulation, including anandamide and palmitoylethanolamide. Here, we investigated the effects of pharmacological or genetic FAAH removal on tolerance to the antinociceptive effects of morphine. Experimental Approach: We induced tolerance in male and female mice by administering twice-daily morphine for 7 days while monitoring nociceptive thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…Cannabinoid and opioid systems interact to modulate tail-flick antinociception (Scavone and Van Bockstaele, 2009). Tolerance prevention (Cichewicz and Welch, 2003;Fotio et al, 2020) as well as cross-tolerance between exogenous cannabinoid agonists and morphine have been reported in non-human primates (Gerak et al, 2015) and rats (Altun et al, 2015a,b). In otherwise naïve rats, intra-PAG injection of the cannabinoid receptor agonist HU-210 enhanced morphineinduced antinociception and prevented morphine tolerance in the tail-flick test (Wilson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoid and opioid systems interact to modulate tail-flick antinociception (Scavone and Van Bockstaele, 2009). Tolerance prevention (Cichewicz and Welch, 2003;Fotio et al, 2020) as well as cross-tolerance between exogenous cannabinoid agonists and morphine have been reported in non-human primates (Gerak et al, 2015) and rats (Altun et al, 2015a,b). In otherwise naïve rats, intra-PAG injection of the cannabinoid receptor agonist HU-210 enhanced morphineinduced antinociception and prevented morphine tolerance in the tail-flick test (Wilson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic dosing of morphine (twice daily 20 mg/kg, except day 1, for 13 days) resulted in tolerance to the hypolocomotor and the anti-nociceptive, but not to the hyperthermic, effects of morphine, as has been reported to the anti-nociceptive effects of morphine by Fotio et al (2020). Here rats were injected with OlGly (5 mg/kg, ip, Experiment 1) or OlAla (5 mg/kg ip, Experiment 2) prior to each chronic treatment with morphine or saline to determine if these fatty acid amides that act in vitro as FAAH inhibitors and PPARα agonists (Donvito et al, 2019;Ayoub et al, 2020), would interfere with morphine tolerance as has been reported for the FAAH inhibitor, URB597 (Fotio et al, 2020). However, at least at a dose of 5 mg/kg, ip, neither OlGly nor OlAla administration interfered with the establishment of tolerance to the anti-nocicieptive and the hypolocomotor effects of morphine.…”
Section: Discussionmentioning
confidence: 66%
“…Unlike OlGly and OlAla, the FAAH inhibitor URB597, has recently been shown to prevent tolerance to morphine antinociception in the tail flick test using a similar procedure and dosing schedule as was used here (Fotio et al, 2020). The effect of URB597 on morphine tolerance was reversed by pretreatment with a cannabinoid 2 (CB 2 ) receptor antagonist (AM630) and partially suppressed by pretreatment with a FIGURE 2 | OlAla (A) the mean (± sem) distance (cm) traveled in the locomotion test, (B) the mean (± sem) latency to tail flick from a hot water bath, (C) mean (± sem) body temperature ( • F), displayed by the various groups across the 13 days of chronic morphine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, repeated administration of morphine for 15 days was associated with tolerance to its analgesic activity as evidenced by the significant decrease in the latency time observed at day 15 of morphine administration compared to its effect on day 1. The development of tolerance following repeated morphine administration was previously reported (Fotio, Palese et al 2020).…”
Section: Discussionmentioning
confidence: 86%